Water hyacinth-derived cellulose biocomposites: extraction methods, physicomechanical properties, and sustainable applications — a review - Siddiqui, Vasi Uddin; Jailani, Azrol; Habib, Abdul; Hidzer, M. Hazim; Usmani, Farah; Azka, Muhammad Adlan; Suffian, Muhammad Irfan; Saifulazmi, Muhammad Arif; Sapuan, S. M.; Mahardika, Melbi; Kadriadi, .; Abral, Hairul (Elsevier, 2025)
Water hyacinth (Eichhornia crassipes), an invasive aquatic plant, has emerged as a promising bioresource for sustainable composite development. However, its rapid proliferation causes severe ecological disruptions, necessitating innovative valorization strategies. This review aims to explore the feasibility of using water hyacinth fibers in biocomposites by assessing their properties, fabrication methods, and application potential. Various fiber extraction and composite fabrication techniques, including chemical treatments (e.g., alkali, silane) and molding processes, are evaluated for their effectiveness. Results show that chemical treatments significantly enhance mechanical performance: tensile strength increases from 20-30 MPa (untreated) to 40-60 MPa, flexural strength reaches up to 80 MPa, and elastic modulus improves to 8 GPa in hybrid composites. Treated fibers also reduce water absorption from 25 % to below 10 % and improve thermal degradation temperature from 200 °C to 420 °C. Additionally, sound absorption and vibration damping characteristics exceed those of conventional materials, with sound absorption coefficients surpassing Styrofoam. Applications span biodegradable packaging, textiles, thermal insulation, and environmental remediation. Despite limitations in moisture sensitivity and mechanical strength, water hyacinth composites demonstrate substantial potential for circular bioeconomy applications. This review consolidates current knowledge and highlights research gaps critical for advancing their scalability and commercialization.